2020
DOI: 10.3390/ijms21239217
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein Derivatives as Fluorescent Probes for pH Monitoring along Recent Biological Applications

Abstract: Potential of hydrogen (pH) is one of the most relevant parameters characterizing aqueous solutions. In biology, pH is intrinsically linked to cellular life since all metabolic pathways are implicated into ionic flows. In that way, determination of local pH offers a unique and major opportunity to increase our understanding of biological systems. Whereas the most common technique to obtain these data in analytical chemistry is to directly measure potential between two electrodes, in biological systems, this inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(75 citation statements)
references
References 104 publications
0
75
0
Order By: Relevance
“…The plot of the ratio of the integrated FI of FITC and NR as function of pH (Fig. 2g, inset) yields a pKa value of 7.47 ± 0.02 that is slightly shifted to basic pH values compared to unbound FITC (pKa value of 6.5) 39 . This shift is attributed to the coupling of FITC to a negatively charged particle 40 .…”
Section: Resultsmentioning
confidence: 97%
“…The plot of the ratio of the integrated FI of FITC and NR as function of pH (Fig. 2g, inset) yields a pKa value of 7.47 ± 0.02 that is slightly shifted to basic pH values compared to unbound FITC (pKa value of 6.5) 39 . This shift is attributed to the coupling of FITC to a negatively charged particle 40 .…”
Section: Resultsmentioning
confidence: 97%
“…Both tartrazine and fluorescein are well‐known dyes, the first commonly used as pharmaceutical and food colorant, [13,14] while the second is a broadly used fluorescent probe in biological and biochemical applications [15,16] . Unlike tartrazine, fluorescein and its derivatives can exist in aqueous solution in a number of prototropic forms: cationic, neutral, monoanionic and di‐anionic (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, ELISA revealed that with speci c parameters, EA stimulation increased the amount of exogenous NGF in the brain under physiological and pathological conditions but did not affect the physical structure of the BBB, which is important for preserving cellular integrity and the health of the brain and the CNS (42). To visually observe the passage of NGF across the BBB, we labeled the primary amine group of NGF with FITC, establishing a stable urea bond covalently to form FITC-NGF (43). In general, FITC-NGF emits yellow-green uorescence that permits tracing of the bonded NGF.…”
Section: Discussionmentioning
confidence: 99%